2019
DOI: 10.31386/dmj.2019.13.1.6
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Profile in Subclinical Hypothyroidism: A Two Centers Experience

Abstract: Background: Subclinical hypothyroidism (SCH) is estimated to affect around 7.5-8.5% of females and 2.8-4.4% of males. One of the features of clinical hypothyroidism is dyslipidemia. There is a great debate about the presence of abnormal lipid profiles in patients with subclinical hypothyroidism (SCH) and weather it is clinically significant or not. Some evidences show reduction in the level of the serum lipid profile after replacement with thyroid hormones. The purpose of this study is to estimate the prevalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 1 publication
2
4
0
Order By: Relevance
“…A number of studies have reported that SCH is associated with increased risk of coronary heart diseases and results in significant increase in cluster of cardiometabolic risk factors. [13,14] Similar to earlier studies, we also found preponderance of cardiometabolic risk factors in subjects with SCH in comparison to euthyroid subjects. In subjects with SH, there is a significant increase in diastolic blood pressure, total, and LDL cholesterol as well as fasting blood sugar levels.…”
Section: Discussionsupporting
confidence: 91%
“…A number of studies have reported that SCH is associated with increased risk of coronary heart diseases and results in significant increase in cluster of cardiometabolic risk factors. [13,14] Similar to earlier studies, we also found preponderance of cardiometabolic risk factors in subjects with SCH in comparison to euthyroid subjects. In subjects with SH, there is a significant increase in diastolic blood pressure, total, and LDL cholesterol as well as fasting blood sugar levels.…”
Section: Discussionsupporting
confidence: 91%
“…Our study also found an increase in lipid profiles (TC,TG, LDL) and decrease in (HDL) in hypothyroidism patients which agrees with an earlier study, wherein they report a high increase in LDL, TC levels in 88 women aged 20-35 years with hypothyroidism at Misan City as compared to control (14). Also result in agreement with (14) found increase in (LDL) low density lipoprotein and decrease in (HDL) HDLs are increased risks factors for cardiovascular diseases (CVD) due to endothelial dysfunction, coagulation disturbances metabolic, hormonal, and hemodynamic changes related with altered lipid profile (10). A statistical significant link observed between high blood TC, TG, LDL, and low HDL levels among patients in this study, is consistent with an earlier study (15), wherein it was reported that the increase in LDL, TC and TG of hypothyroidism may be related to secretion of thyroid hormones which in turn can have an effect on the metabolism of HDL by transfer of cholesterol ester transfer protein (CETP) from (HDL2) to very low density lipoproteins (VLDL) and TG (13) found highly increase statically (p≤0.0001) in TC, LDL while decrease in (HDL) but there is no any significant change in TG associated to control (3).…”
Section: Discussionsupporting
confidence: 89%
“…Studies have shown that that the pituitary gland secretes thyroid stimulating hormone as a result of the negative feedback process. High levels of T3/T4 exert a negative feedback on the anterior pituitary decreasing TSH secretion, while low levels of T3/T4 increase TSH serum concentrations (10).…”
Section: Discussionmentioning
confidence: 99%
“…Paulo et al found high prevalence (62%) of hypovitaminosis D among Brazilians with type 2 diabetes as compared to control. However, Nielsen, et al from United States did not support an association between low vitamin D levels and risk of type 2 diabetes [ 4 , [16] , [17] , [18] , [19] ].…”
Section: Discussionmentioning
confidence: 99%